Hispanics in the United States, the racist Arizona lawand immigration reform promised by Obama - Calvo-Buezas, Tomás (Universidad Pedagógica y Tecnológica de Colombia, 2013)
Hispanics in USA are about to become the largest minority with a very strong personality cultural and an own cultural profile, hardly assimilable. The immigrant law in Arizona is an attack on this minority in a State that was formerly Mexican. Hispanics voted 67% to Obama and expect from him a fair immigration law reform. Depending on which, they will vote or not to the next presidential elections in 2012